2021
DOI: 10.1101/2021.09.07.459151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A copper switch for inducing CRISPR/Cas9-based transcriptional activation tightly regulates gene expression in Nicotiana benthamiana

Abstract: CRISPR-based programmable transcriptional activators (PTAs) are used in plants for rewiring gene networks. Better tuning of their activity in a time and dose-dependent manner should allow precise control of gene expression. Here, we report the optimization of a Copper Inducible system called CI-switch for conditional gene activation in Nicotiana benthamiana. In the presence of copper, the copper-responsive factor CUP2 undergoes a conformational change and binds a DNA motif named copper-binding site (CBS). In t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Owing to its proven responsiveness to dCasEV2.1, and especially the low basal expression levels observed in repeated experiments, we decided to use the p SlDFR structure as the basis for the design of a new set of dCasEV2.1-regulated synthetic promoters (Figure 1C). A “minimal promoter” element was designed by selecting the region comprising the 5’UTR and the TATA box from the SlDFR gene (named mDFR) as previously reported by Garcia-Perez et al 21 . This element was assigned a standard A3(−B2) position, according to the Phytobrick syntax, thus being flanked by TCCC and AATG overhangs (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to its proven responsiveness to dCasEV2.1, and especially the low basal expression levels observed in repeated experiments, we decided to use the p SlDFR structure as the basis for the design of a new set of dCasEV2.1-regulated synthetic promoters (Figure 1C). A “minimal promoter” element was designed by selecting the region comprising the 5’UTR and the TATA box from the SlDFR gene (named mDFR) as previously reported by Garcia-Perez et al 21 . This element was assigned a standard A3(−B2) position, according to the Phytobrick syntax, thus being flanked by TCCC and AATG overhangs (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…These results position the GB_SynP collection as a promising tool for the regulation of complex multigene circuits with different gRNAs present in the cis-regulatory boxes of each promoter, thus creating logic gates that could be useful to further explore different metabolic fluxes within biosynthetic pathways. Moreover, other studies reported the successful expression of gRNAs under pol-II promoters, which in turn could be regulated by different inducers 21,27 , thus allowing customizable control of each gRNA with different stimuli to further direct the multigene circuits in different ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation